Negara Hukum dan Demokrasi dalam Perspektif Konstitusional - Afifa Rangkuti (Al-Muqaranah : Jurnal Perbandingan Hukum dan Mazhab, 2026)
This study aims to analyze the normative construction and interrelation between the principles of the rule of law and democracy within the Indonesian constitutional system. The rule of law and democracy constitute two fundamental pillars affirmed in the 1945 Constitution of the Republic of Indonesia, particularly through the provisions on constitutional supremacy and popular sovereignty. This research employs a normative legal method using statutory and conceptual approaches, based on library research of primary and secondary legal materials. The analysis is conducted descriptively and analytically to examine constitutional supremacy, legality, separation of powers, checks and balances, protection of human rights, and public participation in law-making and governance. The findings reveal that the rule of law provides a normative framework to limit and control state power, while democracy ensures political legitimacy in the formation and implementation of law. Both principles are complementary and essential in establishing a just, participatory, and civilized government. Nevertheless, practical challenges remain, requiring the strengthening of legal institutions and the deepening of substantive democracy to fully realize constitutional ideals. spasi.